Special physical training of athletes in the specialty Kyokushin kata within the framework of the program of additional education - Efimova O. S., Petrygin S. B. (Competence approach in education: trends and challenges)
The implementation of additional education as sports training requires a special approach to students. It is necessary to take into account the level of basic training of students that differs from sports schools. The article develops a step-by-step plan for mastering the technical training of Kyokushin karate for the system of additional education.
Keywords: дополнительное образование; ката; kata; karate kyokushinkai; карате киокусинкай; сфп